Does the Thymus Index Predict COVID-19 Severity?. Issue 2 (13th March 2023) - Berkan, Ocal; Kiziloğlu, Ilker; Keles, Ercan; Duman, Lale; Bozkurt, Mehmet; Adibelli, Zehra; Oncel, Guray; Berkan, Nevsin; Ekemen Keles, Yildiz; Jones, Jeremy H.; Inan, Abdurrahman Hamdi; Solak, Cihan; et al.
Abstract : Background: The COVID-19 (coronavirus disease 2019) pandemic is a global health emergency that is straining health care resources. Identifying patients likely to experience severe illness would allow more targeted use of resources. This study aimed to investigate the association between the thymus index (TI) on thorax computed tomography (CT) and prognosis in patients with COVID-19. Methods: A multicenter, cross-sectional, retrospective study was conducted between March 17 and June 30, 2020, in patients with confirmed COVID-19. The patients' clinical history and laboratory data were collected after receiving a signed consent form. Four experienced radiologists who were blinded to each other and patient data performed image evaluation. The appearance of the thymus was assessed in each patient using 2 published systems, including the TI and thymic morphology. Exclusion criteria were lack of initial diagnostic thoracic CT, previous sternotomy, pregnancy, and inappropriate images for thymic evaluation. A total of 2588 patients with confirmed COVID-19 and 1231 of these with appropriate thoracic CT imaging were included. Multivariable analysis was performed to predict the risk of severe disease and mortality. Results: The median age was 45 (interquartile range, 33–58) years; 52.2% were male. Two hundred forty-nine (20.2%) patients had severe disease, and 60 (4.9%) patients died. Thymus index was significantly associated with mortality and severe disease (odds ratios, 0.289 [95% confidence interval, 0.141–0.588; P = 0.001]; and 0.266 [95% confidence interval, 0.075–0.932; P = 0.038]), respectively. Perithymic lymphadenopathy on CT imaging had a significantly strong association with grades of TI in patients with severe disease and death ( V = 0.413 P = 0.017; and V = 0.261 P = 0.002, respectively). A morphologically assessable thymus increased the probability of survival by 17-fold and the absence of severe disease by 12-fold. Conclusion: Assessment of the thymus in patients with COVID-19 may provide useful prognostic data for both disease severity and mortality.